Management of Okra Shoot and Fruit Borer Earias vitella (Fab.) by Different Insecticides on Okra - Yadav, Anil Kumar; Choudhary, A.K.; B.Gangwar; Kumar, Pradeep; Yadav, Ajay Kumar; Yadav, Mahendra; Harsoliya, Jitendra; Yadav, Kamal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The okra shoot and fruit borer (Earias vittella) is a significant pest affecting okra crops. It bores into the shoots and fruits, causing stunted growth and reduced yield. To combat this pest the present study was conducted during Kharif, 2023 at Rainfed Agriculture Research Farm, Department of Entomology, Bundelkhand University Jhansi. The investigation was carried out to evaluate the efficacy of different insecticides against okra shoot and fruit borer Earias vitella (Fab.), Nine insecticides including control (untreated) were sprayed three times on the okra crop resulted all treatments were significantly effective over control. Among all treatments emamectin benzoate 5% SG was found best effective to control the shoot and fruit infestation caused by E. vitella in all three sprays followed by fluebendiaminde 480% EC and spinosad 45% SC. Among all treatments maximum C:B ratio was obtained from the emamectin benzoate 5% SG (147.56 qt/hac and 1:1.57) followed by spinosad 45% SC (1:1.46), indoxacarb 14.5% SC (1:1.37).